2014
DOI: 10.1016/j.joca.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Development and reliability of a multi-modality scoring system for evaluation of disease progression in pre-clinical models of osteoarthritis: celecoxib may possess disease-modifying properties

Abstract: We report the development of a sensitive and reliable multi-modality scoring system, the RAKSS, for evaluation of OA severity in pre-clinical animal models. Using this scoring system, we found that celecoxib prevented enlargement of osteophytes in this animal model of PTOA, and thus it may be useful in preventing OA progression. However, it did not show any chondroprotective effect using the recommended dose. In contrast, high dose glucosamine had no measurable effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…These findings are consistent with those of previous studies in other animal models 17,21 . However, unlike some previous studies 15,16 , the results failed to demonstrate smaller osteophytes in CLX-treated animals than in the MNX group. This may be due to the small sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those of previous studies in other animal models 17,21 . However, unlike some previous studies 15,16 , the results failed to demonstrate smaller osteophytes in CLX-treated animals than in the MNX group. This may be due to the small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…It has little effect on joint space narrowing in humans 14 . However, animal experiments have shown that CLX still has effects in mitigation of joint degeneration by reducing osteophyte development 15 . This could be explained by a previous study showing that CLX could decrease RANKL synthesis and subsequently increase the OPG/RANKL ratio in the cartilage which may further affect subchondral bone metabolism 16 .…”
Section: Introductionmentioning
confidence: 99%
“…OA is characterized by erosion of articular cartilage and subchondral bone sclerosis [Panahifar et al, ]. To control the progression of the OA, pharmacological and dietary methods have been used [Kaneva et al, ; Xu et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…22e26 In ACLT þ Medial collateral ligament transaction (MCLT) þ Medial meniscus resection (Mx), the surgical procedure aims to preserve the integrity of the posterior cruciate ligament, and the rest of procedures are the same as in the traditional Hulth model. 27,28 In cruciate ligament transection (CLT), the surgical approach is to only remove the anterior cruciate ligament; the rest of the static structure was not touched. In view of the above-mentioned various modeling methods, all of the methods focus on the joint instability pathway by destroying the joint stability structure and aggravating articular surface wear as well as using other surgical techniques to simulate the human PTOA process.…”
Section: Hulth Model/modified Hulth Model (4/34)mentioning
confidence: 99%